Optimization of some Mineral Contents of Dried Osmo-pretreated Green Bell Pepper (Capsicum annuum) using Reponse Surface Methodology - Odewole, M. M.; Sunmonu, M. O.; Oyeniyi, S. K.; Adeyinka-Ajiboye, O.; Ayodimeji, Z. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2012)
A study to optimize three mineral contents (magnesium, potassium and manganese) of dried osmo-pretreated green bell pepper was done using Response Surface Methodology (RSM). Five levels of osmotic solution concentration (A) (5% (w/w), 10% (w/w), 15% (w/w), 20% (w/w) and 25% (w/w)) of common salt and osmotic process durations (B) (60 min, 90 min, 120 min, 150 min and 180 min) were considered. After osmotic dehydration, all pre-treated and some control (unpre-treated) samples were dried at a constant temperature of 50˚C in a fabricated cabinet dryer. RSM under central composite design in Design Expert 8.0.3 computer software package was used to design the experiment, analyse data, optimize the process and present all results with 2-dimesional and 3-dimensional plots. From results obtained, optimized combinations were selected on the basis of their desirability values which were 0.931, 0.432 and 1.00 for magnesium, potassium and manganese respectively. From the desirability values on the response surface plots, the optimum (maximum) value of magnesium was found to be 29.18 mg/100g at osmotic process duration of 180 min and osmotic solution concentration of 25% (w/w); for potassium, the optimized value was 46.13 mg/100g at osmotic process duration of 60 min and osmotic solution concentrationo f 5% (w/w); while the optimized value for manganese was 10.96 mg/100g at osmotic process duration of 150 min and osmotic solution concentration of 15% (w/w). Dried pre-treated products had values closer to fresh samples than controld (Dried unpre-treated) samples for all the three mineral contents considered.